TEACHER COMPETENCY IMPROVEMENT STRATEGY IN FACING THE CHALLENGES OF 21ST CENTURY EDUCATION AT MTS LKMD SAWA BURU-MALUKU - Yasmin Afifah; Asmawati Lapandewa; Muhammad Syafi’i Tampubolon (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study focuses on MTs LKMD Sawa, Buru Regency, Maluku, using a descriptive qualitative approach to explore the challenges and strategies for improving teacher competence in facing the dynamics of 21st century education. The results of the study were obtained through in-depth interviews with teachers and the head of the madrasah. The findings indicate that teachers face significant challenges, such as limited technological facilities, disparities in digital literacy, a lack of practice-based instruction, and declining student motivation to learn. Strategies implemented to address these challenges include continuous training, teacher collaboration, the use of digital media, and value-based and contextual learning approaches. The integration of technology and humanistic pedagogical approaches is key to shaping adaptive and relevant teachers. This study concludes that teacher professional development must be collaborative, contextual, and continuous. With institutional support and reflective awareness from teachers, the educational process will become more meaningful and transformative. This study also recommends strengthening the digital ecosystem in madrasahs and involving teacher learning communities as the main pillars of competency transformation in the digital era. These findings highlight the importance of collaboration between teachers and institutions in addressing educational transformation in the digital era. This study is expected to serve as a reference for educational institutions in designing strategies to enhance teacher competencies that are relevant to contemporary challenges.